Aplikasi Emulsi (O/W) Berbagai Konsentrasi Minyak Kelapa Sawit sebagai Edible Coating pada Buah Tomat (Solanum lycopersicum L.) - Mutia, Reiza; Rifqah, Rahil Ade; Antika, Via Afriani (Agriculture Faculty, 2024)
Palm oil in the form of oil in water (o/w) emulsion could be used as edible coating to extend the shelf life of agricultural commodities. The objectives of this research were to study the effect of edible coating in the form of oil in water emulsion (o/w) from various palm oil concentrations on tomatos quality and to find the best concentration. This research used Block Randomized Design with a treatment of palm oil concentration, including: P1 (control), P2 (1%), P3 (5%), P4 (25%) and P5 (30%). Observed parameters were weight loss (%), hardness value (mm/10 seconds), total dissolved solid value (Brix) and damage intensity (%). Edible coating from palm oil emulsion could maintain the quality of tomato up to a concentration of 25%. The P3 emulsion was the best treatment because it resulted low percentage of weight loss (22.03%); highest value of hardness (2.42 mm/10 sec); highest value of total dissolved solids (3.33Brix), and lowest percentage of damage intensity (1.83%) during 24 days storage time. Overall, the application of edible coating in the form of palm oil emulsion (o/w) was able to maintain the quality of tomatoes six days longer than without it.